(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In the early stages of maize (Zea mays L.) development, it is important to limit weeds that compete with maize for nutrients, moisture, light. Weed control has various methods, for example, agrotechnical, chemical. The aim of the study is to evaluate of the Effects of Weeds and Hybrids on the Productivity of Maize grain in Ukraine. The research was conducted in field conditions in 2019-2021 at the Mykolayiv National Agrarian University, which is located in the southern steppe of Ukraine. The results of the study show that weeds significantly (P<0.05) reduced the maize grain yield. During the grain harvesting period, the number of weeds in GS 89 decreased to 137 and 121 weeds m-2. In the experiment, the predominance of early summer weeds (more than 66%) over late summer weeds (about 49%) was found. Effective weed reduction requires the use of several agrotechnical elements. Grain yield of maize hybrids increased significantly in areas where herbicides were applied. The corn hybrid 'Gran 6' was more productive. Maize hybrid Gran 6 is 1.3 times more productive than maize hybrid Odesskii 385 МВ in all test variants, which was also influenced by the hybrids' biological differences: maize hybrid Gran 6 has a shorter vegetation period and is taller (on average 209.1 cm) than maize hybrid Odesskii 385 МВ, which is 198.0 cm tall on average. Moisture consumption differed in vegetation years (2019-2021), the highest was in 2021 (70.6%), when a higher corn grain yield was also established.